2014
DOI: 10.1111/cen.12492
|View full text |Cite
|
Sign up to set email alerts
|

Increased concentration of T‐cell receptor rearrangement excision circles (TREC) in peripheral blood in Graves' disease

Abstract: Patients with GD, particularly those with hyperthyroidism, have increased concentration of TREC which may suggest increased rather than decreased thymic activity. Thus, GD does not follow the paradigm suggested for other autoimmune disorders which links autoimmunity with thymic senescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 33 publications
(78 reference statements)
0
7
1
Order By: Relevance
“…Examination of the decrease in the number of sjTREC molecules caused by thymus involution occurring in the course of human life has a predictive capacity and has been implemented in forensic age prediction [ 33 ]. Our investigation of age predictive DNA methylation markers does not support a conclusion that can be drawn from the study performed by Strawa about younger age of GD patients [ 32 ]. A hypomethylation of the FHL2 gene predicts younger age of patients, but two other markers (TRIM59 and KLF14) have increased methylation comparing to the controls, while ELOVL2 and C1orf132 are unchanged.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Examination of the decrease in the number of sjTREC molecules caused by thymus involution occurring in the course of human life has a predictive capacity and has been implemented in forensic age prediction [ 33 ]. Our investigation of age predictive DNA methylation markers does not support a conclusion that can be drawn from the study performed by Strawa about younger age of GD patients [ 32 ]. A hypomethylation of the FHL2 gene predicts younger age of patients, but two other markers (TRIM59 and KLF14) have increased methylation comparing to the controls, while ELOVL2 and C1orf132 are unchanged.…”
Section: Discussioncontrasting
confidence: 93%
“…Antibody-driven activation of the thyrotropin receptor leads to hyperfunction of the thyroid gland and thyroid enlargement and in consequence increased production of the thyroid hormone [ 31 ]. Previous study investigated T cell receptor rearrangement excision circle (sjTREC) concentration in Graves’ disease patients and reported that although generally decreasing with age, it was significantly higher in GD group compared with controls [ 32 ]. Examination of the decrease in the number of sjTREC molecules caused by thymus involution occurring in the course of human life has a predictive capacity and has been implemented in forensic age prediction [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Impaired central tolerance in autoimmune endocrine disorders is a relatively new concept. However, up to this date, only a few studies have investigated circulating TRECs in patients with T1D [15], Hashimoto thyroiditis [36], and Graves disease [16, 37], and there are no data regarding KREC measurement in any autoimmune endocrine disorders. Hofer et al [15] observed increased circulating TRECs in 38 patients with T1D with mean age of 10 to 15 years.…”
Section: Discussionmentioning
confidence: 99%
“…The primer sequences for TREC assay were designed by Primer-3 software (National Center for Biotechnology Information, Bethesda, MD), whereas the probe was described earlier by Douek et al [28]. Primers and probe for KRECs were described earlier by Sottini et al [29] and those for albumin gene by Strawa et al [16]. The sequences of the primers, fluorescent probes, and amplicon sizes are given in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation